Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 12 - Cumulative Review: 30


$x^{3}\sqrt[3] x$

Work Step by Step

$\sqrt[3] x^{10}=\sqrt[3] (x^{9}\times x)=\sqrt[3] x^{9}\times\sqrt[3] x=x^{3}\sqrt[3] x$ We know that $\sqrt[3] x^{9}=x^{3}$, because $(x^{3})^{3}=x^{3\times3}=x^{9}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.